Kontribusi Pemungutan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Bogor - Dede Suleman (Universitas Bina Sarana Informatika, 2018)
one of the local taxes is the acquisition of land and building rights (BPHTB) which is a component of revenue in regional revenue. in this case usually the amount of its target acquisition has been calculated every year. but there could be a difference between the number of targets and receipts each year in because many factors here the authors compare the target and acceptance and ontribusinya to the regional income in bogor district 2012-2016. The effectiveness of this tax revenue is an assessment of the performance of the Department of Revenue (Dipenda) kabupateb Bogor. Tax revenue has been called effective if acceptance in accordance with the potential that has been determined BPHTB effectiveness in 2014 amounted to 131.72% and in 2015 of 114.46% decreased from 2014 and in 2016 of 124.60% increased from 2015. and can be concluded in 2014 is the year where the effectiveness of BPHTB is the largest in the number of percentage, but in terms of the largest revenue in 2016. BPTHB contribution to Local Revenue in 2014 amounted to 7.59%, while in 2015 at 6.05% and can be categorized in terms of percentage contribution has decreased but in terms of revenue increased from 2014. And in the year contribution of BPHTB 2016 amounted to 8.45% and can be said the largest since 2014 both in terms of percentage and in terms of revenue, but in 2016 PAD decreased revenue from the year 2015.